2009
DOI: 10.1136/ip.2008.020180
|View full text |Cite
|
Sign up to set email alerts
|

Non-firearm-related homicide, New Mexico, 2001–3

Abstract: Homicide-prevention efforts among AIs in NM should focus on non-firearm-related homicides. The association between excessive drinking and non-firearm-related homicide should be further characterised. Continued surveillance for non-firearm-related homicides will assist these efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Despite these results, there was a significant increase in odds of alcohol‐involved victimization in nonfirearm homicides, particularly among victims with a BAC ≥ 0.08%. This is consistent with a study of nonfirearm related homicides in New Mexico, in which victims of nonfirearm homicides with a BAC ≥ 0.08% had significantly increased odds of victimization (Kazerouni et al., ). Additionally, this study found also that a far greater proportion of American Indians had impairment‐level BACs compared to victims of other races.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite these results, there was a significant increase in odds of alcohol‐involved victimization in nonfirearm homicides, particularly among victims with a BAC ≥ 0.08%. This is consistent with a study of nonfirearm related homicides in New Mexico, in which victims of nonfirearm homicides with a BAC ≥ 0.08% had significantly increased odds of victimization (Kazerouni et al., ). Additionally, this study found also that a far greater proportion of American Indians had impairment‐level BACs compared to victims of other races.…”
Section: Discussionsupporting
confidence: 90%
“…A study analyzing 10 years of data in Los Angeles in the 1970s found that when the victim and perpetrator were known to one another, alcohol was detected in the victim in 38 to 53% of cases (Goodman et al., ). More recently, in a study comparing firearm to nonfirearm homicides in New Mexico, a BAC ≥ 0.08% was detected in 43% of nonfirearm homicide victims, 61% of whom were American Indians (Kazerouni et al., ).…”
mentioning
confidence: 99%
“…But much research, such as that by Hunt and Cowling (1991) or Delice and Yasar (2013), emphasizes the significant portion of knife violence that is a result of domestic disputes. This is probably why Kazerouni et al (2009) found most knife homicides involved male offenders and female victims. For that reason, the authors do not expect to see the same trends for victims and perpetrators in regard to gender.…”
Section: Hypothesesmentioning
confidence: 99%
“…This is not to say the topic has never been addressed. Kazerouni et al (2009) performed an in-depth comparison of firearm and non-firearm homicides in the state of New Mexico. This is because New Mexico has a greater concentration of non-firearm related homicides (47% of homicide victims) than the national average (33% of homicide victims) (Kazerouni et al, 2009).…”
Section: International Literature On Knife Violencementioning
confidence: 99%
See 1 more Smart Citation